EXPLORING TREND OF TECHNOLOGY INTEGRATED IN TBLT FOR ENHANCING EFL LEARNERS SPEAKING SKILLS: A SYSTEMATIC REVIEW IN INDONESIAN EFL CONTEXT - Nayla Azzahra; Zuliati Rohmah (CALL, 2026)
The fast incorporation of digital tools into language instruction has transformed speaking pedagogy in EFL classrooms. This systematic literature review maps recent trends, task types, educational levels, and publication pattern in technology-integrated Task-Based Language Teaching (TBLT) for speaking instruction in Indonesia. Guided by PRISMA procedures, empirical studies published between 2020–2025 and indexed in SINTA 1–4 were gathered from Open Knowledge Maps and manual journal database searches. A total of 593 records (39 from Open Knowledge Maps and 564 from 129 journals from SINTA database) were initially identified. Out of the initial pool, 16 studies met the inclusion criteria and were analyzed using qualitative thematic synthesis. The synthesis reveals a significant paradigm shift from traditional, spontaneous classroom interactions before 2020 toward technology-mediated, reflective, and product-oriented task designs post-2020. Among the identified tasks, digital video recording emerges as the most dominant type (6 studies), which foster authentic audience engagement and learner autonomy. Traditional tasks like role-play remain present (7 studies), while a notable gap is identified where 2 studies failed to explicitly define their task parameters. Geographically and institutionally, research heavily clusters around secondary and higher education levels, leaving a critical methodological deficit in primary education. These findings offer crucial pedagogical implications for Indonesian EFL practitioners. It is important to emphasize that technology is intended to facilitate meaningful communication instead of being used simply as a source of novelty. Furthermore, it highlights the need for balanced future research addressing younger learners and performance-based outcomes over mere perception data